2018
DOI: 10.3389/fimmu.2017.01915
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 27a-3p Regulates Antimicrobial Responses of Murine Macrophages Infected by Mycobacterium avium subspecies paratuberculosis by Targeting Interleukin-10 and TGF-β-Activated Protein Kinase 1 Binding Protein 2

Abstract: Mycobacterium avium subspecies paratuberculosis (MAP) persistently survive and replicate in mononuclear phagocytic cells by adopting various strategies to subvert host immune response. Interleukin-10 (IL-10) upregulation via inhibition of macrophage bactericidal activity is a critical step for MAP survival and pathogenesis within the host cell. Mitogen-activated protein kinase p38 signaling cascade plays a crucial role in the elevation of IL-10 and progression of MAP pathogenesis. The contribution of microRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 94 publications
1
27
0
Order By: Relevance
“…BCG upregulates the expression of miR-20a leading to the downregulation of its target protein ATG7 and ATG16L1, a process that could prevent autophagy (Guo et al, 2016 ). In addition, miR-27a activate macrophage responses to control intracellular survival of Mycobacterium avium subspecies paratuberculosis by targeting TAB2 and IL-10 mRNA (Hussain et al, 2018 ). Early study reported that M. bovis infection upregulate the expression of miR-146a and miR-146b in alveolar macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…BCG upregulates the expression of miR-20a leading to the downregulation of its target protein ATG7 and ATG16L1, a process that could prevent autophagy (Guo et al, 2016 ). In addition, miR-27a activate macrophage responses to control intracellular survival of Mycobacterium avium subspecies paratuberculosis by targeting TAB2 and IL-10 mRNA (Hussain et al, 2018 ). Early study reported that M. bovis infection upregulate the expression of miR-146a and miR-146b in alveolar macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the macrophages were moved to 6 or 12-well cell culture plates for 12–18 h prior to transfection and/or infection. Previously reported protocols were followed for isolation and culture of mouse bone marrow-derived macrophages (BMDMs) [51]. Briefly, femurs and tibia of 6 to 8 weeks-old female C57BL/6 mice were used to sequester undifferentiated bone marrow cells.…”
Section: Methodsmentioning
confidence: 99%
“…miR-27b augmented the cellular responses against infection with pathogens by suppressing the expression of several target genes, including interleukin (IL)-10, transforming growth factor (TGF)-β-activated protein kinase 1 binding protein 2 (Tab. 2), and Frizzled7 (FZD7) [38, 41]. Several members of the Herpesviridae family express a miR-27 inhibitor for infection [37, 42].…”
Section: Discussionmentioning
confidence: 99%